Diversity and structure of soil bacterial communities in the Fildes Region (maritime Antarctica) as revealed by 454 pyrosequencing - Wang, Neng Fei; Zhang, Tao; Zhang, Fang; Wang, En Tao; He, Jian Feng; Ding, Hui; Zhang, Bo Tao; Liu, Jie; Ran, Xiang Bin; Zang, Jia Ye (Frontiers in Microbiology, 2015)
This study assessed the diversity and composition of bacterial communities in four different soils (human-, penguin-, seal-colony impacted soils and pristine soil) in the Fildes Region (King George Island, Antarctica) using 454 pyrosequencing with bacterial-specific primers targeting the 16S rRNA gene. Proteobacteria, Actinobacteria, Acidobacteria, and Verrucomicrobia were abundant phyla in almost all the soil samples. The four types of soils were significantly different in geochemical properties and bacterial community structure. Thermotogae, Cyanobacteria, Fibrobacteres, Deinococcus-Thermus, and Chlorobi obviously varied in their abundance among the 4 soil types. Considering all the samples together, members of the genera Gaiella, Chloracidobacterium, Nitrospira, Polaromonas, Gemmatimonas, Sphingomonas and Chthoniobacter were found to predominate, whereas members of the genera Chamaesiphon, Herbaspirillum, Hirschia, Nevskia, Nitrosococcus, Rhodococcus, Rhodomicrobium, and Xanthomonas varied obviously in their abundance among the four soil types. Distance-based redundancy analysis revealed that pH (p < 0.01), phosphate phosphorus (p < 0.01), organic carbon (p < 0.05), and organic nitrogen (p < 0.05) were the most significant factors that correlated with the community distribution of soil bacteria. To our knowledge, this is the first study to explore the soil bacterial communities in human-, penguin-, and seal- colony impacted soils from ice-free areas in maritime Antarctica using high-throughput pyrosequencing.